If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + -5n = 5n + 8(4n + 4) Reorder the terms: -10 + -5n = 5n + 8(4 + 4n) -10 + -5n = 5n + (4 * 8 + 4n * 8) -10 + -5n = 5n + (32 + 32n) Reorder the terms: -10 + -5n = 32 + 5n + 32n Combine like terms: 5n + 32n = 37n -10 + -5n = 32 + 37n Solving -10 + -5n = 32 + 37n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-37n' to each side of the equation. -10 + -5n + -37n = 32 + 37n + -37n Combine like terms: -5n + -37n = -42n -10 + -42n = 32 + 37n + -37n Combine like terms: 37n + -37n = 0 -10 + -42n = 32 + 0 -10 + -42n = 32 Add '10' to each side of the equation. -10 + 10 + -42n = 32 + 10 Combine like terms: -10 + 10 = 0 0 + -42n = 32 + 10 -42n = 32 + 10 Combine like terms: 32 + 10 = 42 -42n = 42 Divide each side by '-42'. n = -1 Simplifying n = -1
| 3/3y=?/20-8y | | (20/x)=50 | | 603/12.7=1210/n | | 25y(3y+2x)= | | 3x/4-1/2=1/4 | | -6g+22=-3g+8g | | -7x+1=7x-139 | | 72-2x-3=46 | | -8(1+8k)-8k=-8-5k | | -10+6+2x=100 | | 72x-2x-3=46 | | -9g+30=-6g+7g | | (3x-3)+3(4x+8)=4x-1 | | 0.44(x+6)=8 | | 1/8=1/1/8/n | | 7w+2w-1=4w+9 | | 15x=3(4x+24) | | N-6=2*4 | | f(x)=0.97+4.5x | | 3x-2(x-1)=-4+3x+10 | | 8=-(-6+n) | | N-6=2*8 | | 6+x+3x=-16 | | 13x=3(2x+28) | | 2(x+4)=32+5x | | (5x+13)=72 | | 14-7p=-7(p-1) | | 14x=3(2x+72) | | (5-3)x(-2)= | | 136=-8(1+6V) | | 14-7p=-7p(p-1) | | 3a-7z=6 |